On the need of a scale-dependent material characterization to describe the mechanical behavior of 3D printed Ti6Al4V custom prostheses using finite element models. (April 2023) - Danielli, Francesca; Ciriello, Luca; La Barbera, Luigi; Rodriguez Matas, Jose Felix; Pennati, Giancarlo
Abstract: Additive manufacturing is widely used in the orthopaedic industry for the high freedom and flexibility in the design and production of personalized custom implants made of Ti6Al4V. Within this context, finite element modeling of 3D printed prostheses is a robust tool both to guide the design phase and to support clinical evaluations, possibly virtually describing the in-vivo behavior of the implant. Given realistic scenarios, a suitable description of the overall implant's mechanical behavior is unavoidable. Considering typical custom prostheses' designs (i.e. acetabular and hemipelvis implants), complex designs involving solid and/or trabeculated parts, and material distribution at different scales hinder a high-fidelity modeling of the prostheses. Moreover, uncertainties in the production and in the material characterization of small parts approaching the accuracy limit of the additive manufacturing technology still exist. While recent works suggest that the mechanical properties of thin 3D-printed parts may be peculiarly affected by specific processing parameters (i.e. powder grain size, printing orientation, samples' thickness) as compared to conventional Ti6Al4V alloy, the current numerical models make gross simplifications in describing the complex material behavior of each part at different scales. The present study focuses on two patient-specific acetabular and hemipelvis prostheses, with the aim of experimentally characterizing and numerically describing the dependency of the mechanical behavior of 3D printed parts on their peculiar scale, therefore, overcoming one major limitation of current numerical models. Coupling experimental activities with finite element analyses, the authors initially characterized 3D printed Ti6Al4V dog-bone samples at different scales, representative of the main material components of the investigated prostheses. Afterwards, the authors implemented the characterized material behaviors into finite element models to compare the implications of adopting scale-dependent vs. conventional scaleindependent approaches in predicting the experimental mechanical behavior of the prostheses in terms of their overall stiffness and the local strain distribution. The material characterization results highlighted the need for a scale-dependent reduction of the elastic modulus for thin samples compared to the conventional Ti6Al4V, which is fundamental to properly describe the overall stiffness and local strain distribution on the prostheses. The presented works demonstrate how an appropriate material characterization and a scale-dependent material description is needed to develop reliable FE models of 3D printed implants characterized by a complex material distribution at different scales. Graphical abstract: Image 1 Highlights: The study analyzed 3D printed custom acetabular and hemipelvis prostheses. The material characterization highlighted a scale-dependent effect on elastic modulus. Prostheses' FE models were developed, and scale-dependent materials were assigned. Scale-dependent FE models better predicted the stiffness and the strains on the prostheses. Scale-dependent FE models accurately described the mechanical behavior of 3D printed custom prostheses.